Fetal Outcomes on The Maternity Do Prenatal Gentle Yoga in Mataram - Nurul Qamariah Rista Andaruni; Rizkia Amilia; Indriyani Makmun; Ana Pujianti Harahap (Jurnal Kebidanan, 2022)
Pregnancy and delivery in a mother is a process that natural. Natural process this to run smoothly needed physical activity. Yoga is physical activity have the effect of the physical individuals do yoga and helping pregnant women to reach balance lives and also prompted a good physical the baby ( fauziah l.2016 ). Research aims to understand on the fetal outcome on the maternity do prenatal gentle yoga in mataram. A method of this research is descriptive and the total sample in this research as many as 29 respondents to technique the sample used is the total the sampling method of as well as data taken using a questionnaire and a record of observation. The results showed that the fetal outcome in as a weight of a newborn infant are normal 29 respondents ( as many as 100 % ), the body length of a newborn infant all are normal respondents ( as many as 27 % 93,1 ), Asphyxia in newborn infants are categorized not asphyxia as many as 26 respondents ( 89.7 % ), the temperature of the body of the newborn categorized as normal as many as 29 respondents ( 100 % ), hemoglobin levels of a newborn infant not anemia are categorized as many as 22 respondents ( 75,9 % ). Conclusions from the results of research obtained almost all fetal outcome in a new baby seem normal. Are expected to carry out research komparasi to long duration gymnastic yoga for pregnant to see significant impact on a new baby born and the condition of pregnant mothers during pregnant.